Social Support and Quality of Life Among Older Adults in South Kalimantan, Indonesia: A Cross-Sectional Study - Catharina Guinda Diannita; Veronica Paula; Maria Maxmila Yoche Arkianti; Ballsy Cicilia Albertina Pangkey; Suntoro Suntoro; Shema Christy Noya Simamora (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2026)
Globally, many countries are experiencing population ageing and will continue to do so over the next several decades, including Indonesia. As the world’s population ages, there will be a growing demand for health care services that improve the quality of life as well as longevity. In ageing populations, the desire to spend the most advanced years in a good self-assessed health condition has gained more relevance. To cope with the challenges arising from this trend, most older adults prefer to remain in their familiar environment in the community and live with some level of independence. The purpose of this study is to analyze the corelation between social support and quality of life among older adults. A cross-sectional study was conducted with 94 respondens aged 59 and above. Data were collected using validated instruments Medical Outcomes Study Social Support Survey (MOS-SSS) and World Health Organization Quality of Life–BREF (WHOQOL-BREF) Indonesian version. IBM SPSS 29.0 software was used for Spearman’s rank correlation test. The study results indicate that there is a significant correlation between social support and QoL. these results underscore the importance of interventions aimed at strengthening social networks, promoting family involvement, and fostering community empowerment as strategies to improve community quality of life.